2018
DOI: 10.1016/j.gene.2018.05.110
|View full text |Cite
|
Sign up to set email alerts
|

Molecular network, pathway, and functional analysis of time-dependent gene changes related to cathepsin G exposure in neonatal rat cardiomyocytes

Abstract: The molecular pathways activated in response to acute cathepsin G (CG) exposure, as well as the mechanisms involved in activation of signaling pathways that culminate in myocyte detachment and apoptosis remain unclear. This study aimed to determine the changes in gene expression patterns associated with time dependent CG exposure to neonatal rat cardiomyocytes (NRCMs). Microarray analysis revealed a total of 451, 572 and 1127 differentially expressed genes after CG exposure at 1, 4 and 8 h respectively. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It has previously been shown that cleaved Slamf7 promotes the growth of multiple myeloma (Kikuchi et al, 2020) and that inhibition of SLAMF7 blocks adhesion of multiple myeloma cells to bone marrow stromal cells (Bouchon et al, 2001;Hsi et al, 2008). Slamf7 has been found to regulate PLCγ and PI 3 K in human NK cells (Tassi and Colonna, 2005) and to be upregulated in cultured neonatal cardiomyocytes following acute cathepsin G exposure (Shukla et al, 2018). These findings suggest that Slamf7 can be present in cardiomyocytes and that it responds to various stresses.…”
Section: Discussionmentioning
confidence: 91%
“…It has previously been shown that cleaved Slamf7 promotes the growth of multiple myeloma (Kikuchi et al, 2020) and that inhibition of SLAMF7 blocks adhesion of multiple myeloma cells to bone marrow stromal cells (Bouchon et al, 2001;Hsi et al, 2008). Slamf7 has been found to regulate PLCγ and PI 3 K in human NK cells (Tassi and Colonna, 2005) and to be upregulated in cultured neonatal cardiomyocytes following acute cathepsin G exposure (Shukla et al, 2018). These findings suggest that Slamf7 can be present in cardiomyocytes and that it responds to various stresses.…”
Section: Discussionmentioning
confidence: 91%
“…Given the limitations of H9c2 cardiomyocytes, neonatal rat cardiomyocytes (NRCMs), considered common models for studying the morphological, biochemical, and electrophysiological characteristics of the heart ( Chlopcikova et al, 2001 ), were obtained from 2-3 day-old Sprague–Dawley (SD) rats (Beijing Si Pei Fu Biotechnology, Certificate SCXK-2019-0010) after strict sterilization by the methodology used for isolation and cultivation in previous research, with some modifications ( Sabri et al, 2003 ; Rafiq et al, 2006 ; Shukla et al, 2018 ). The apex of isolated heart tissue was digested repeatedly in the short term in a mixture of collagenase II (Biorigin Inc., China) and 0.25% trypsin (Gibco Life Technologies, China) with a magnetic stirrer at 37°C.…”
Section: Methodsmentioning
confidence: 99%